Determinación del impacto de la roya en el cultivo de cebada (Hordeum vulgare L.) y sus alternativas de control, en la Parroquia El Ángel, Provincia del Carchi - Portilla Muñoz, María Guadalupe (2019)
SUMMARY The present work was carried out in the Corner Espejo, Province of Carchi, with the purpose of determining the impact of the rust on the barley crop, this investigation was carried out through the method of direct observation in the field, performing monitoring and diagnosing the spread of the disease in the barley crop. The rust is characterized by the appearance of orange-brown pustules that advance along the nerves of the leaves toward the tips, the yellow rust on the barley has been a problem that has caused significant losses in production, because the fungus can evolve and cause crop losses and represent significant economic losses for farmers. In the same way, for the survey of primary information, surveys were carried out to the farmers of the barley crop, to determine the factors of dissemination of the pathogen, the damages caused and the management practices applied. The results obtained indicate that 75% of the area of the barley crop has been attacked by rust, due to the climatic conditions prevailing in the area; the crop attacked has mainly presented blister-like lesions of yellow color in the leaves organized in stripes caused by the fungus Puccinia striiformis; the damage in the crop is high, this because 70% of the producers do not apply preventive measures. To control the attack of the pathogen, most farmers make biweekly applications of fungicides. In conclusion, due to the ignorance of the farmers of the Parroquia El Ángel about the technical management of the cultivated crop the attack of yellow rust in frequent, to this the climatic conditions, the use of seed of not certified and the scarce application of measures are added preventive to avoid the attack of the pathogen. Key words: Yellow rust, pathogen, farmers, barley.